Severity of Childhood Asthma Among Normal, Overweight and Obese Children - A Comparative Study - Nishkala Uday Rao; Pushpalatha Kariyappa; Vaibhav S. Bellary (Galenos Yayinevi, 2023)
Aim:To determine the severity of asthma among asthmatic children with a) normal body mass index (BMI), b) and those who are overweight or obese. To compare the severity of asthma among children with normal BMI, and those who are overweight and obese.Materials and Methods:One hundred and fifty asthmatic children meeting the diagnostic criteria were enrolled onto this study. Thorough clinical and anthropometric examinations were carried out. The children were then categorized into two groups based on their BMI as either those with normal BMI or those who were overweight/obese. They were then followed up over 12 months and the information collected was analyzed.Results:Of the 150 children, 72% were male and 45.3% belonged to the age group of 6-11 years. In 46.7%, asthma was diagnosed <5 years. 50% of the children missed school for between 1 and 5 days per year. The majority (63.3%) of the asthmatic children were able to perform the same level of physical activity as their peers. 54% of the asthmatic children had mild persistent asthma. Overweight/obesity was present in 19.3% of the participants. The majority (72.4%) of the obese asthmatic children were diagnosed <12 years and had moderate-severe persistent asthma. Those asthmatic children who were overweight or obese had more frequent night awakenings and missed more school days at enrolment and during follow-up. The overweight/obese asthmatic children visited the emergency department, required rescue medications and received steroids more often than those children with normal BMI.Conclusion:Obese asthma is a well-defined phenotype of childhood asthma, characterized by higher disease burden and poor response to treatment. Hence, a two-pronged strategy to tackle being overweight or obese and also to manage the asthma in this group is warranted with strategies directed towards reductions in obesity at an early age in order to help reduce the severity of their asthma.